Effect of phosphorus and determination of optimum nitrogen for bread wheat in Kofele District, West Arsi Zone of Oromia, Ethiopia - Firomsa, Tilahun; Husien, Abdurahman; Assefa, Kafyalew; Abera, Tilahun; Lemma, Amante; Hundessa, Chali (Journal of Scientific Agriculture, 2020)
Optimum nutrients are basic for proper and balanced fertilizer recommendations as paramount importance in order to confirm food security and increase crop productivity in a sustainable way for farmers and other stakeholders. Soil test based crop response phosphorus calibration study for bread wheat at kofole district in 2016 with objectives to determine the optimum nitrogen of bread wheat to nitrogen-fertilizer applications in soils and to give quantitative guidelines and recommendations of nitrogen-fertilizer for bread wheat on Eutric Vertisols. The study was conducted on farmers’ fields across the district. The treatments considered for optimum nitrogen determination were four levels of nitrogen (0, 46, 69 & 92) and phosphorus (0, 23, 46 & 92) fertilizer included in the treatments. The treatments were arranged in a factorial combination of complete block design with two replications. The plot size of 5mx4m with a seed rate of 150kg/ha a variety of Ogolcho which had been recommended for the area was used. The analysis of variance showed that there were significant differences (p<0.05) among treatments application for all locations. The highest grain yield was obtained on the application 69N kg/ha with no application of phosphorus fertilizers on Eutric Vertisols. Minimum grain yield was obtained on the control plots at all sites. Optimum determination with the partial budget analysis made using the annual average bread wheat grains prices showed that 69 kg N ha-1 gave a marginal rate of return of 122.41%, which is above the acceptable minimum rate of return. Therefore, future research should focus on soil test crop response based phosphorus calibration study of on the result optimum nitrogen of the farmland could be a pre request of the technology before to the end user.